Importance of service quality dimensions at guest arrival area implements by five stars hotel in Seri Kembangan and Putrajaya / Anidah Aziz, Lina Mazwein Ibrahim and Zahariah Sahudin - Aziz, Anidah; Ibrahim, Lina Mazwein; Sahudin, Zahariah (2009)
The research is regarding "Importance of service quality dimensions at guest arrival area implements by five stars hotel in Seri Kembangan and Putrajaya", According to Parasuraman (1991), service quality has five dimensions, which are tangibles, responsiveness, reliability, assurance, and empathy. These dimensions are important to measure the quality of the service. The aim of this research is to identify importance service quality dimensions at guest arrival area implements by the five-star hotels in Seri Kembangan and Putrajaya. The research is also to determine the improvement that need to be implement in the guest arrival in order to enhance the service quality of these five-star hotels. The questionnaires have been distributed to 200 respondents which are the guest of the selected five-star hotels by using convenience sampling. In the research, there are three objectives. First objective is to identify the most importance service quality dimensions at guest arrival area implements by the five-star hotels in Seri Kembangan and Putrajaya. The second objective is to determine the respondents' level of importance towards service quality at guest arrival area for each type of service quality dimensions at guest arrival area implements by the five-star hotels in Seri Kembangan and Putrajaya. The last objective is to identify the relationship between selected respondent profile and service quality dimensions at guest arrival area implements by the five-star hotels in Seri Kembangan and Putrajaya. The researcher have used SPSS program version 15.0 where the researcher have used frequency analysis, descriptive analysis, reliability testing, cross tabulation in order to interpret the data.